Urgensi Pendidikan Karakter Bagi Generasi Z Sebagai Solusi Tanggap Terhadap Tantangan Kompleks Era VUCA - Alamin, Nurul Salis; Irma Lupita Sari; Hidayahsyah, Nurul (Sehati Abdimas, 2023)
Generation Z is a demographic that grew up and developed in the digital era. Generation Z, which has grown up in the digital era and is exposed to a variety of information, is faced with challenges such as job uncertainty, changing social values, and the complexity of global interactions or what is often called VUCA (Volatile, Uncertain, Complex, Ambiguous). Rapid changes in technology, globalization, and social dynamics give rise to an urgent need to prepare this generation holistically. Character education emerges as a crucial approach in shaping Generation Z's moral and ethical foundation. Generation Z, as a group that is technologically active and exposed to rapid social changes, needs a strong foundation of character to face the challenges of an uncertain and unpredictable life. This research aims to explore and formulate relevant and effective character education strategies to equip Generation Z with adaptability, moral leadership, and psychological resilience in facing the challenges of the VUCA era. This type of research is library research. The result of this research is the internalization of religious values in millennial generation character education in facing the challenges of the VUCA era. Therefore, this research is important in helping to create an educational environment that supports positive character development and the readiness of the millennial generation to face the complexity of challenges in the VUCA era.